(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Different percentages (2.5%, 5% and 7.5%) of rosemary leaves powder were added to local wheat flour(80% extraction), to study the result of adding this herb on the rheological properties of dough. To reach this target, Farinograph was used to study the water absorption, dough development time, dough stability and degree of dough softening, the out come was compared with local wheat flour with out addition. The obtained results showed that local wheat had values of water absorption, dough stability approximate to those of the local wheat flour after adding the percent of 2.5 and 5% of degree dough softening from rosemary leaves powder. The water absorption, dough development time of local wheat flour was improved as a function of adding rosemary to the flour. The increase rosemary is forming, which helped include The water absorption, dough development time of local wheat flour. It can be concluded that rosemary leaves powder was able to improve the rheological properties of local wheat flour at (2.5% and 5%)and a good quality loaf.